2014
DOI: 10.1002/adfm.201401534
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Sensitive Adhesion of an Elastomeric Protein Complex Extracted From Squid Ring Teeth

Abstract: The pressure sensitive adhesion characteristic of a protein complex extracted from squid ring teeth (SRT), which exhibits an unusual and reversible transition from a solid to a melt, is studied. The native SRT is an elastomeric protein complex that has standard amino acids, and it does not function as adhesives in nature. The SRT can be thermally shaped into any 3D geometry (e.g., thin films, ribbons, colloids), and it has a glass transition temperature of 32 °C in water. Underwater adhesion strength of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…The absorption peak in this region is related to the aromatic ring in the side chains of Tyr and His. Tyr and His are likely to contribute strongly to this band, because their amino acid fractions are 15.3% and 4.9%, respectively, for the synthetic polypeptides compared with 15.4% and 9.2%, respectively, for the recombinant 18-kDa SRT protein (9) and 12.5% and 10.9%, respectively, for the native SRT protein from L. vulgaris (11). A triplet of bands (marked as β in SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption peak in this region is related to the aromatic ring in the side chains of Tyr and His. Tyr and His are likely to contribute strongly to this band, because their amino acid fractions are 15.3% and 4.9%, respectively, for the synthetic polypeptides compared with 15.4% and 9.2%, respectively, for the recombinant 18-kDa SRT protein (9) and 12.5% and 10.9%, respectively, for the native SRT protein from L. vulgaris (11). A triplet of bands (marked as β in SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using the tools of molecular biology and proteomics, it has been shown that these squid ring teeth (SRT) proteins have segmented semicrystalline morphology with repetitive amorphous and crystalline domains. SRT-based materials were shown to have high elastic modulus: 4-8 GPa in air and 2-4 GPa underwater below the glass transition temperature (11). However, a clear relationship between the molecular structure and the mechanical properties of this material remains elusive.…”
mentioning
confidence: 99%
“…Native SRT (16) and silk (17) proteins were extracted from the tentacles of Loligo vulgaris and cocoons of Bombyx mori respectively following the protocol reported earlier. The proteins were dissolved in organic solvents and processed for deposition of pure polymeric protein films as described in Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…The rings are composed of a group of repetitive proteins, ranging from 15 to 60 kDa, which have a segmented sequence topology similar to semi-crystalline segmented copolymers (22,23). The repetitive sequence favors the formation of a beta-sheet-rich cross-links that confers unique mechanical (24), adhesive (25), thermal (26), optical (27), and self-healing (28) properties to SRT. Furthermore, SRT is easily processed by solution and thermal fabrication methods into nano to macro protein-based materials, from nanotubes and nanoparticles to large-scale objects (25).…”
Section: Introductionmentioning
confidence: 99%